Strategi Pengembangan Ekowisata Bumi Perkemahan Ledok Ombo Kec. Poncokusumo Kab. Malang - Putri, Adinda Amalia; Puspitasari, Amanda Wahyu; Lestari, Ayu Puji; Anggraini, Apririya; Rachmadan, Aditya Arief (Innovative: Journal Of Social Science Research, 2025)
This study aims to formulate a development strategy for Ledok Ombo Ecotourism in Poncokusumo District, Malang Regency. Ledok Ombo possesses great potential as a natural tourism destination with its preserved pine forest landscape and cool air. However, it faces challenges such as limited facilities, suboptimal promotion, and the absence of dedicated tourism management. The research uses qualitative methods through interviews, observations, and documentation involving local managers and community members. SWOT analysis was employed to identify strengths, weaknesses, opportunities, and threats. The IFE and EFE analysis results position Ledok Ombo in the “Hold and Maintain” strategy quadrant, recommending enhanced promotion, facility development, and formation of a dedicated management team. Implementing appropriate strategies is expected to support the sustainability and competitiveness of Ledok Ombo Ecotourism.